What is a BSM? - Consorcio para el Desarrollo Sostenible de la Ecorregion Andina (CONDESAN, 2013)
Benefit-Sharing Mechanisms (BSMs) work to redistribute the benefits of a healthy watershed equitably to everyone and to create a virtuous circle between the welfare of people and the ecosystems they live in.